2013
DOI: 10.1177/0956797612457386
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Can Reduce Age-Related Forgetting

Abstract: In three experiments, we assessed whether older adults' generally greater tendency to process distracting information can be used to minimize widely reported age-related differences in forgetting. Younger and older adults studied and recalled a list of words on an initial test and again on a surprise test after a 15-min delay. In the middle (Experiments 1a and 2) or at the end (Experiment 3) of the delay, participants completed a 1-back task in which half of the studied words appeared as distractors. Across al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
84
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 41 publications
13
84
2
Order By: Relevance
“…Previously, our group has argued that older adults can make beneficial use of distraction, and that implicit rehearsal can actually selectively benefit older adults (e.g. Healey et al, 2008;Biss et al, 2013)-from this perspective, the CRUNCH hypothesis is certainly plausible. Within the current experiment however, participants were instructed to ignore distractors -a goal that was better maintained by the young and old AM groups.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, our group has argued that older adults can make beneficial use of distraction, and that implicit rehearsal can actually selectively benefit older adults (e.g. Healey et al, 2008;Biss et al, 2013)-from this perspective, the CRUNCH hypothesis is certainly plausible. Within the current experiment however, participants were instructed to ignore distractors -a goal that was better maintained by the young and old AM groups.…”
Section: Discussionmentioning
confidence: 92%
“…An interesting follow-up to this study could examine the effect of DA at retrieval during an explicit task measuring transfer of distraction (e.g. Biss et al, 2013), as explicit memory may be more susceptible to effects of unconstrained retrieval. One of the goals of this research is to characterize the mechanism of the distraction transfer effect that has been shown to benefit memory in older adults (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, young and older participants performed a selective attention task on pictures, ignoring superimposed distracter words, and older adults outperformed young adults on a subsequent word fragment completion task in which previous distracter words served as solutions to some fragments (Rowe et al, 2006). Older adults' implicit knowledge of distraction has now been shown to transfer to a variety of other test tasks including cued recall (Campbell, Hasher, & Thomas, 2010;Weeks, Biss, Murphy, & Hasher, 2016), prospective memory (Lourenço & Maylor, 2015), and free recall (Biss, Ngo, Hasher, Campbell, & Rowe, 2013), all without participants reporting any awareness of the relevance of the distracters. It is currently unclear whether the observed tacit transfer of distraction to later tasks is related to a lack of attentional control at encoding, retrieval, or both.…”
mentioning
confidence: 99%
“…Rabbitt concluded that older adults have greater difficulty ignoring irrelevant information compared with their younger counterparts and suggested based on some of his previous work that this may be due to a reduced efficiency of perceptual grouping. Although the way in which we carry out and describe research has certainly changed since then (e.g., in his paper, stimuli were stenciled onto cards that participants manually sorted, participants were referred to as Ss in the manuscript), the ability of older adults to ignore irrelevant information and both the hindrances, as well as the surprising advantages of them doing so is still a topic of much interest today (e.g., Biss, Ngo, Hasher, Campbell, & Rowe, 2013;Weeks & Hasher, 2014).…”
Section: Emergence Of Cognitive Aging Theory: the Mid-1960smentioning
confidence: 99%